Celebrating the 100th Anniversary of Madame Marie Sklodowska Curie$1 (Bs Nobel Prize in Chemistrys - Chiu, M.-H.; Gilmer, P. J.; Treagust, D. F.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
This book is a companion to the IYC-2011 celebration. The eleven chapters are organized into three sections: Section 1: Marie Curie$1 (Bs Impact on Science and Society, Section 2: Women Chemists in the Past Two Centuries, and Section 3: Policy Implications. The authors invited to contribute to this book were asked to orient their chapter around a particular aspect of Marie Curie$1 (Bs life such as the ethical aspects of her research, women$1 (Bs role in research or her influence on the image of chemists. Our hope is that this book will positively influence young women$1 (Bs minds and decisions they make in learning of chemistry/science like Marie Curie$1 (Bs biography. But we do hope this book opens an avenue for young women to explore the possibility of being a scientist, or at least to appreciate chemistry as a human enterprise that has its merit in contributing to sustainability in our world. Also we hope that both men and women will realize that women are fully competent and capable of conducting creative and fascinating scientific research.s
Keywords: Education; Science -- Study and teaching; Education; Science Education